The Porbandar cyclone of October 1975 - GUPTA, G. R.; MISHRA , D. K.; YADAV, B. R. (MAUSAM, 1977)
A severe cyclonic storm formed-over the east central Arabian Sea, from the remnants of an earlier depression over the Bay of Bengal, and crossed north Gujarat coast near Porbandar at 1530 IST On 22 October 1975. This cyclone showed rapid intensification during its formative stages and was singular for its track and, severity. A detailed study of the information, movement and intensity of the storm has been made m this paper on the basis of the synoptic as well as Weather satellite data. It is concluded that the thermal structure of the cyclone and the marked upper tropospheric divergence observational net- were responsible for its rapid intensification.